DESIGN OF FIRE DETECTION AND ALARM SYSTEM USING PLC SCADA FOR SHOPPING MALL (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
PLC (Programmable logic controller) has now become a phenomenon concept when it comes to safety and long term product usability. In this paper we have presented design of fire security system based on programmable logic controller, several design guidelines have been shown in this paper. Also critical issues like selecting appropriate sensor and PLC has also been mentioned. Also a strict observation of the type of PLC used and its advantage are highlighted throughout the paper